EFEKTIFITAS MANAJEMEN AKTIF KALA IV TERHADAP RISIKO PERDARAHAN PADA PASIEN POST OPERASI SECTIO CAESAREA DI RUMAH SAKIT - Sartika Jaya; Sri Wahyuni; Apriliani Yulianti Wurningsih (Yayasan Healing and Healthcare Education, 2026)
Postpartum hemorrhage is a major cause of maternal morbidity and mortality, including in post-cesarean section patients. The fourth stage is a critical phase in the first two hours after delivery that requires intensive monitoring to prevent bleeding. Objective: To determine the effectiveness of active management of the fourth stage on the risk of bleeding in post-cesarean section patients. Method: This study used a quasi-experimental design with a post-test only approach with a control group. The sample consisted of 40 post-cesarean section mothers who were divided into an intervention group and a control group using a consecutive sampling technique. The intervention was in the form of implementing active management of the fourth stage during the first two hours after surgery. The variables measured included the amount of bleeding, decreased hemoglobin levels, and the incidence of postpartum hemorrhage. Data analysis used independent t-test and chi-square tests with a significance level of 0.05. Results: There was a significant difference in the amount of bleeding and decreased hemoglobin levels between the intervention and control groups (p < 0.05). The incidence of postpartum hemorrhage was lower in the group receiving active management of the fourth stage of labor. Conclusion: Active management of the fourth stage of labor effectively reduces the risk of bleeding in post-cesarean section patients and is recommended as part of standard postpartum nursing care.